GREEN DUAL-CHANNEL SUPPLY CHAIN MODEL WITH CONSIDERING PRODUCT RETURNS AND REMANUFACTURING PROCESS - Amelia, Cynthia Rizky; Setiyowati, Ririn; Sutanto, Sutanto (PATTIMURA UNIVERSITY, 2023)
The development of information and communication technology causes internet users to increase, so consumers are increasingly accustomed to buying products through online channels. This can encourage business people to carry out a sales strategy using two channels (offline and online) or commonly called Dual-Channel Supply Chain (DCSC). In its application, it is hoped that business people will create an environmentally friendly company to reduce carbon emissions. Therefore, business people create companies that implement the Green Dual-Channel Supply Chain (GDCSC) model. GDCSC in online channels has one drawback, namely that consumers cannot evaluate products accurately. This allows consumers to obtain defective products resulting in product returns. Returned defective products can be reprocessed through the remanufacturing process. To provide solutions to these conditions, centralization scenario is used to determine the optimal solution so that maximum profit is obtained. Based on the analysis, it shows that changes in price elasticity and product returns cause system profits to get smaller, while changes in price elasticity and energy efficiency levels cause system profits to get bigger.